OTORITAS PEMERINTAH DAERAH ATAS AGRARI TERHADAP...HAK...ULAYAT. .MASYARAKAT..HUKUM. ADAT.BERDASARKAN..OTONOMI DAERAH - Mangapul Marbun; Syawal Amry Siregar (JURNAL RETENTUM, 2020)
Regional government authorities have been regulated since the inception of UU..No..22. 1999, in which. This legislation has been amended several times, namely: .UU5. No. 32. Year. 2004, Law no. 23 of 2014,. And Law, No. 9 of 2015 Regarding Regional Government, that is Regional Autonomy in the administration of government in the regions. As regulated in article 1 point 2, article 1 point 6, and article 12 paragraph (2) which in this case relates to the authority of the Regional Government regarding land. Article 3 and article 5 of the UUPA, have recognized the existence of customary rights of the customary law community, but the 2014 legislation has not been implemented. Regarding the recognition and protection of customary law, which is confirmed in article 1 point 1, article 1 point 2, and article 2, and article 3. The Regional Government will carry out the responsibility to place recognition and protection of the rights of customary communities throughout Indonesia, which still have the customary rights of the local customary law communities. However, the fact is that in the territory of the Unitary State of the Republic of Indonesia, there are still many community rights of customary law communities that have not been recognized by the authority of the local government by making District or City Regulations.